Respon Sporofit Paku Ata (Lygodium circinnatum (Burn. F) Swartz) terhadap Pemberian Pupuk Urea - DWIYANI, RINDANG; YUSWANTI, HESTIN (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012))
Lygodium circinnatum (Burn.f.) Swartz is a wild Pteridophyta which is used as a material for handicraft. Recently, Lygodium has been rare in nature due to overgathering. Domestication of this wild plant may required to overcome this problem. A research concerning domestication of Lygodium was conducted at Faculty of Agriculture of Udayana University during March to October 2009. Dose of urea fertilizer in varied levels was applied to 8 month-old sphorophyte. The level of urea doses were 0, 100, 200, 300 and 400 mg urea per plant. The results showed that urea fertilizer significantly stimulated the number of “sulur” (“sulur” is an organ of Lygodium that used as material for handicraft) , but did not affect the number of leaves and plant height. Dose of 300mg urea per plant resulted in the highest number of the average of “sulur” number per plant.
Keywords: Lygodium circinnatum (Burn F.) Swartz, urea fertilizer, sulur